Aldol condensation of acyclic ketones with benzaldehyde and subsequent cyclodehydration to form indenes over halide cluster catalysts - Kamiguchi, Satoshi; Nishida, Satoru; Takahashi, Ikuko; Kurokawa, Hideki; Miura, Hiroshi; Chihara, Teiji (Journal of molecular catalysis. A, Chemical, 2006)
A molecular halide cluster [(Ta 6Cl 12)Cl 2(H 2O) 4]·4H 2O catalyzed the aldol condensation of acetone with benzaldehyde to yield E-4-phenyl-3-buten-2-one above 200 °C. 3-Pentanone combined with benzaldehyde provided indenes such as E- and Z-1-ethylidene-2-methylindene, by cyclodehydration of the aldol condensation product, E-2-methyl-1-phenyl-1-penten-3-one. One of the advantages of halide cluster catalysts is thermal stability, and high temperatures above 350 °C promoted the cyclodehydration. ▪ When a molecular halide cluster [(Ta 6Cl 12)Cl 2(H 2O) 4]·4H 2O ( 1)/SiO 2 was treated in a helium stream above 200 °C, it catalyzed the aldol condensation of acetone with benzaldehyde to yield E-4-phenyl-3-buten-2-one. The bromide cluster of Ta and chloride clusters of Nb, Mo, and W of the same octahedral metal framework also catalyzed the reaction. 3,3-Dimethyl-2-butanone combined with benzaldehyde similarly yielded the corresponding aldol condensation product over 1/SiO 2 at 400 °C. On the other hand, 3-pentanone combined with benzaldehyde provided indenes such as E- and Z-1-ethylidene-2-methylindene and 2-methyl-3-vinylindene of the same carbon skeletal structure, which would be formed by cyclodehydration of the aldol condensation product, E-2-methyl-1-phenyl-1-penten-3-one. One of the advantages of halide cluster catalysts is thermal stability, and high temperatures above 350 °C promoted the cyclodehydration.